SCOPE OF APPLICABILITY OF THE COMPETENCE APPROACH IN EDUCATION - Oleg R. Kayumov (Moscow Polytechnic University, 2016)
The article considers the natural obstacles to the implementation of the competence approach in Russian higher education. They are caused by extrasystemic (regardless of pedagogy) genesis of the concept of «competence », which is rather cost estimation category in the labor market and is not a constructive parameter, at least in the intermediate stages of mid-term assessment in higher education institution. An attempt to use Western descriptors (in the framework of the «Bologna obligations») in Russia proved to be inefficient due to the significant disparities in education systems, which have different civilizational roots. From a pedagogical point of view the recurrent (as in the experiments of the 1920s) mixing of the «activity» and «learning » is a didactic nihilism, and not «a competence paradigm ». The scope of applicability of the competence-based approach in domestic conditions should be limited to a few specializations with a strong «executive » specifics, but for the most educational profiles should not go beyond the final certification and the previous work experience or internship.